Arts and Humanities Citation Index for Research Evaluation in the Field of Religion: Unusual Findings and Suggestions - Zhang, Ruifeng (Journal of religion and health, 2026)
The Arts & Humanities Citation Index (A&HCI) is widely used for research evaluation, including in the field of Religion. However, apart from merely indexing research output published in journals, it is still unclear what other flaws exist when using this authoritative database to evaluate religion-related studies. Through a comprehensive analysis of the A&HCI data from a full 50-year period and the most recent 10-year period, we uncover a series of unusual findings in the field of Religion, including stagnation in the number of indexed records, absence of the author's address information, anomalies of the main contributing countries/regions, and over-concentration of preferred journals. We discuss the challenges posed by these unusual findings to the evaluation of religion-related studies using the A&HCI database. This study concludes with suggestions to the relevant stakeholders to address these issues.